Fractal Electrochemical Microsupercapacitors. (17th August 2017) - Hota, Mrinal K.; Jiang, Qiu; Mashraei, Yousof; Salama, Khaled N.; Alshareef, Husam N.
Abstract: The first successful fabrication of microsupercapacitors (μ‐SCs) using fractal electrode designs is reported. Using sputtered anhydrous RuO2 thin‐film electrodes as prototypes, μ‐SCs are fabricated using Hilbert, Peano, and Moore fractal designs, and their performance is compared to conventional interdigital electrode structures. Microsupercapacitor performance, including energy density, areal and volumetric capacitances, changes with fractal electrode geometry. Specifically, the μ‐SCs based on the Moore design show a 32% enhancement in energy density compared to conventional interdigital structures, when compared at the same power density and using the same thin‐film RuO2 electrodes. The energy density of the Moore design is 23.2 mWh cm −3 at a volumetric power density of 769 mW cm −3 . In contrast, the interdigital design shows an energy density of only 17.5 mWh cm −3 at the same power density. We show that active electrode surface area cannot alone explain the increase in capacitance and energy density. We propose that the increase in electrical lines of force, due to edging effects in the fractal electrodes, also contribute to the higher capacitance. This study shows that electrode fractal design is a viable strategy for improving the performance of integrated μ‐SCs that use thin‐film electrodes at no extra processing or fabrication cost. Abstract : Electrochemical supercapacitors fabricated using fractal electrode designs are found to have higher capacitance than conventional interdigital electrode designs. However, changes in the active electrode surface area cannot alone account for the capacitance increase. The increase in electrical lines of force, due to edging effects, are shown to contribute to the enhanced capacitance.